THE INFLUENCE OF PARENTAL ATTENTION ON STUDENT MOTIVATION AT SMA NEGERI 2 TONDANO - Eni Sartika Pane (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
This study aims to determine the effect of parental attention on student learning motivation at SMA Negeri 2 Tondano in the 2020/2021 school year. This research is a quantitative study with a correlational method by means of simple random sampling of 38 students of SMA Negeri 2 Tondano. Data were collected through a questionnaire with a Likert scale. The data analysis technique used simple linear regression analysis with the help of the computer program SPSS 22 for windows. The results of this study indicate that there is an effect of parental attention on student learning motivation obtained by the regression equation Y = 38,277 + 0.397 X with a quantitative increase in the ratio of the two variables is 1: 0.397 this comparison shows that if there is an increase in the value of the parent's attention variable (X) then it will be followed by the level of increase in the value of the student learning activation variable (Y). The regression equation is significant or will not be tested with the Fcount value at the significant level of 0.05. Meaning that Ha was accepted and Ho was rejected. The conclusion is that the hypothesis which says there is an effect of parental attention on student learning motivation at SMA Negeri 2 Tondano is accepted and significant, this is indicated by the value of the regression coefficient (F) of 11.177 with a significant 0.002.